The effect of illiquidity, risk, beta and firm size towards stock returns: ASEAN stock exchanges - Kuswarianto, Ivan; Mahadwartha, Putu Anom; Ernawati, Endang (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
This study investigates the effect of factors related to the stock return, such as liquidity, company size, risk, and beta of companies listed on ASEAN Exchanges for 2011-2019. This study uses a quantitative approach by using multiple linear regression method. The dependent variable is stock return, while the independent variables used are liquidity, company size, risk, and beta. This research uses 14,580 observations of 1,620 wide-spread companies across Indonesia, Malaysia, Thailand, Vietnam, Singapore, and Philippine in nine years. The study finds that illiquidity, risk, and size positively influence stock return significantly, while beta has an insignificant positive effect on stock return. This study also finds that there are country-effect towards stock return in each country.